MEDIA KOLASE BAHAN DAUR ULANG UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI KELOMPOK B TK BINA BUNGA BANGSA SURABAYA - Muflikhah, Felin Nanda Khoirul; Yunitasari, Anisa (Universitas Narotama, 2024)
The fine motor skills of group B TK Bina Bunga Bangsa Surabaya children are still very low. This causes children to be less creative. Fine motor learning at Bina Bunga Bangsa Kindergarten Surabaya is still rarely implemented because the teacher is more focused on calistung which is to prepare children for elementary school. Therefore it is necessary to change the strategy in learning activities. To improve children's fine motor skills. the purpose of this study was to determine the increase in children's fine motor skills using recycled material collage media in group B TK Bina Bunga Bangsa Surabaya. This type of research is Classroom Action Research which consists of several stages consisting of two cycles. Each cycle is held in two meetings. The results of the analysis on the pre cycle average value of 48.88%. In cycle I it achieved an average value of 58.88% and in cycle II it achieved 81.10% success criteria. The conclusion of this study shows that recycled material collage media can improve fine motor skills of early childhood group B TK Bina Bunga Bangsa Surabaya. Keywords: Fine motor skills, Collage Media